The information content in contingent convertible bond prices - Oliver Juhler Grinderslev; Kristian Loft Kristiansen (Danmarks Nationalbank, 2017)
Credit institutions are to an increasing extent using Contingent Convertible Bonds (CoCos) to meet part of their capital requirements, which could suggest that the market for CoCos contains useful information on the robustness of the issuer. This paper gives a thorough introduction to CoCos - the product, its use in capital regulation, the market and the specific risks faced by investors. To illustrate which information potentially can be extracted from the price level and change in prices of CoCos, we introduce models which incorporate most of the characteristics and risks of CoCos. The models illustrate how the complexity of CoCos makes them difficult to use when assessing the soundness of the issuer; in addition to this the many CoCospecific risks make it questionable whether the cost of CoCos constitutes a lower bound for the cost of equity. – – Kreditinstitutter benytter i stigende omfang Contingent Convertible Bonds (CoCo'er) til at opfylde en andel af deres kapitalkrav, hvilket kan gøre markedet for CoCo'er interessant i forhold til at udlede information ominstitutternes robusthed. Denne artikel giver en grundig introduktion til CoCo'er - produktet, dets brug i reguleringen, markedet og de specifikke risici, som investorerne står overfor. Til at illustrere, hvilken information der potentielt kan udledes af CoCo'ernes prisniveau og -ændringer, benytter vi modeller, som inkorporerer de fleste af CoCo'ernes karakteristika og indbyggede risici. Modellerne illustrerer, hvordan kompleksiteten i produktet gør det svært at bruge CoCo'er til at udlede information om udstederens finansielle tilstand, ligesom de mange CoCo-specifikke risici gør det usikkert, om prisen på CoCo'er udgør en nedre grænse for prisen på egenkapital.
Keywords: G01; G12; G21; G23; G28; G32; 330; Financial regulation; Financial stability; Financial sector; Financial risks; Models